2021
DOI: 10.1021/jacsau.1c00142
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Induced Magnetic Skyrmion in a Two-Dimensional Chromium Triiodide Monolayer

Abstract: Chromium iodide monolayers, which have different magnetic properties in comparison to the bulk chromium iodide, have been shown to form skyrmionic states in applied electromagnetic fields or in Janus-layer devices. In this work, we demonstrate that spin-canted solutions can be induced into monolayer chromium iodide by select substitution of iodide atoms with isovalent impurities. Several concentrations and spatial configurations of halide substitutional defects are selected to probe the coupling between the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Remarkably, d ∥ in SL CrInTe 3 (CrInSe 3 ) is rather large, which is calculated to be 4.36 (2.03) meV. Especially for SL CrInTe 3 , d ∥ is significantly large among the values reported in previous studies. ,− , More importantly, the d ∥ / J ratio is found to be 0.165 (0.077) for SL CrInTe 3 (CrInSe 3 ), which is within (near) the typical range of 0.1–0.2 for more likely forming magnetic skyrmion. ,, …”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Remarkably, d ∥ in SL CrInTe 3 (CrInSe 3 ) is rather large, which is calculated to be 4.36 (2.03) meV. Especially for SL CrInTe 3 , d ∥ is significantly large among the values reported in previous studies. ,− , More importantly, the d ∥ / J ratio is found to be 0.165 (0.077) for SL CrInTe 3 (CrInSe 3 ), which is within (near) the typical range of 0.1–0.2 for more likely forming magnetic skyrmion. ,, …”
mentioning
confidence: 59%
“…14,[28][29][30][31]46 More importantly, the d ∥ /J ratio is found to be 0.165 (0.077) for SL CrInTe 3 (CrInSe 3 ), which is within (near) the typical range of 0.1−0.2 for more likely forming magnetic skyrmion. 10,28,47 To get further insight into the DMI in SL CrInX 3 , we project the associated SOC energy ΔE soc [ΔE soc is energy difference between right-and left-hand spin-spiral configurations] on each atom. From Figure 2c, we can see that the main DMI contribution does not originate from the magnetic Cr atoms, but from its adjacent X atoms.…”
Section: S S S S S S S S S Tanmentioning
confidence: 99%
“…[9,18,19] The ability to engineer magnetic properties is valuable for creating spin textures or magnetic ordering for applications in nano-spintronics and memory devices. [20][21][22][23] Recent discoveries of layered vdW magnets [24,25] provide unique opportunities to engineer artificial magnetic phases or textures. [20][21][22][23] However, microscopic studies in archetypal magnets like CrI 3 [24] and CrGeTe 3 [25] have been challenging owing to poor air stability.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Fe 3 GeTe 2 , skyrmions will be destroyed when the thickness is thinner than ≈15 nm, [164] which is unfavorable for downscaling. However, recent theoretical studies have revealed that skyrmions can be created in monolayer and twisted bilayer CrI 3 , [192][193][194][195] which may dramatically improve the downscaling of skyrmion-based devices. Future experiments are required to validate these predictions.…”
Section: Scalabilitymentioning
confidence: 99%